Tinjauan Hukum Kedaulatan Pangan Melalui Kemandirian Petani Berdasarkan Undang-Undang Nomor 19 Tahun 2013 Tentang Perlindungan Dan Pemberdayaan Petani - Jhon Piter Situmeang; Abd. Rahman Saleh (Universitas Moch. Sroedji, 2026)
Farmer Protection and Empowerment aims to realize the sovereignty and independence of farmers in order to improve the welfare, quality, and better life; protect farmers from crop failure and price risks; provide agricultural infrastructure and facilities needed in developing agricultural businesses; develop agricultural financing institutions that serve the interests of agricultural businesses; increase the ability and capacity of farmers and farmer institutions in running productive, advanced, modern, value-added, competitive, market-share and sustainable farming businesses; and provide legal certainty for the implementation of farming businesses. To be able to escape dependence on imported food and alleviate farmers from poverty, it is time for Indonesia to build food independence and sovereignty, by utilizing the diversity of biological resources, restoring local food diversity, and building agricultural-based industries in rural areas. Building food independence and sovereignty is a strategic instrument in efforts to alleviate farmers from poverty. In the implementation of food security programs, the fulfillment of food needs in several sectors still depends on international trade. Building food independence is the best strategy to get out of the food crisis. As an agricultural country with diverse biological resources (biodiversity), Indonesia has significant potential to produce sufficient food. Furthermore, Indonesia has a variety of local foods to support national food diversification